Cancer Detection Rate of MRI Ultrasound Fusion Prostate Biopsy in 1,039 Patients and Number Needed to Biopsy in Targeted Lesion - Choomark, Sivakorn; Aussavavirojekul, Pubordee; Woranisarakul, Varat; Srinualnad, Sittiporn (Siriraj Medical Journal, 2023)
Objective: To determine the cancer detection rate (CDR) of magnetic resonance imaging ultrasound fusion prostate biopsy (MRI/US fusion prostate biopsy) in Thailand. The secondary aim was to estimate the number needed to biopsy (NNB) for each prostate lesion in a targeted biopsy, classified by Prostate Imaging-Reporting and Data System (PI-RADS). Materials and Methods: The data of 1,039 consecutive patients who underwent a MRI/US fusion prostate biopsy at Siriraj Hospital between September 2017 and February 2021 was included and retrospectively reviewed. Those included had previous negative biopsies and were biopsy naïve. The data was analyzed to find the detection rate and NNB. Results: The overall detection rate of MRI/US fusion prostate biopsy was 58.71%, whereas that of systematic biopsy was 45.72%. Clinically significant prostate cancer (csPCa) (Gleason score ≥ 3+4) detection rate of MRI/US fusion prostate biopsy was 51.01%. When categorized by PI-RADS category 3, 4, and 5 were 12.16%, 44.98%, 85.71% respectively. NNB in targeted biopsy of PI-RADS 3, 4, and 5 were 8, 7, and 3 times sequentially. Positive predictive factors for prostate cancer (PCa) detection were age, prostate-specific antigen density (PSAD) and PI-RADS, whereas prostate volume was a negative predictive factor. Conclusion: This study supports the role of MRI/US fusion prostate biopsy in PCa detection and should not avoid systematic biopsies. The higher the PI-RADS was, the greater the csPCa detection rate. NNB is helpful in guiding the least amount of biopsied cores for each lesion.